2021
DOI: 10.1146/annurev-ecolsys-012021-095454
|View full text |Cite
|
Sign up to set email alerts
|

Are Terrestrial Biological Invasions Different in the Tropics?

Abstract: Most biological invasion literature—including syntheses and meta-analyses and the resulting theory—is reported from temperate regions, drawing only minimally from the tropics except for some island systems. The lack of attention to invasions in the tropics results from and reinforces the assumption that tropical ecosystems, and especially the continental tropics, are more resistant to invasions. We have critically assessed biological invasions in the tropics and compared them with temperate regions, finding re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 133 publications
2
39
0
Order By: Relevance
“…In contrast to the Neotropic, the Afrotropic and Oriental regions are understudied, especially given the commonness of biotic dispersal and the frequency of threatened species in these regions (Dirzo et al, 2014;Sridhara et al, 2016;Rogers et al, 2021a). This biogeographic bias mirrors the bias found in research on forest fragmentation and biological invasions, which has been attributed primarily to limited financial resources and political instability (Deikumah et al, 2014;Bellard and Jeschke, 2016;Chong et al, 2021). On the other hand, many studies on abiotic SDD have been carried out in the Palearctic and Nearctic (e.g., De hert et al, 2013;Labatore et al, 2017), probably because abiotic dispersal is more prevalent at higher latitudes (Kling and Ackerly, 2020;Rogers et al, 2021a) and because a good fraction of researchers investigating seed dispersal have home institutions in the temperate realm.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the Neotropic, the Afrotropic and Oriental regions are understudied, especially given the commonness of biotic dispersal and the frequency of threatened species in these regions (Dirzo et al, 2014;Sridhara et al, 2016;Rogers et al, 2021a). This biogeographic bias mirrors the bias found in research on forest fragmentation and biological invasions, which has been attributed primarily to limited financial resources and political instability (Deikumah et al, 2014;Bellard and Jeschke, 2016;Chong et al, 2021). On the other hand, many studies on abiotic SDD have been carried out in the Palearctic and Nearctic (e.g., De hert et al, 2013;Labatore et al, 2017), probably because abiotic dispersal is more prevalent at higher latitudes (Kling and Ackerly, 2020;Rogers et al, 2021a) and because a good fraction of researchers investigating seed dispersal have home institutions in the temperate realm.…”
Section: Discussionmentioning
confidence: 99%
“…Foremost, global analyses suggest severe undersampling and lagging detection of invasive species in LICs and MICs, and/or in the Neotropics, Paleotropics, Asia, and Oceania (39,92,222) where invasions are expected to increase in the future (199). There is a need for aid, resources, and technical assistance from more wealthy nations to address this gap; in fact, such resource pooling is mandated in the SPS agreements (57).…”
Section: Wingfield and Bonellomentioning
confidence: 99%
“…It was thought for a long time that lower reporting of invasions in the tropics was due to biotic resistance, but recent scholarship suggests invasive species are underreported in these often heavily deforested and environmentally degraded, and/or economically poorer parts of the world, i.e. the weakest links, highlighting the need for investment from resource-rich trading partners (39) and free exchange of information. Moreover, success in the fight against climate change, which threatens forests with increased rates of both biotic and abiotic damage, may not be attainable without successful conservation and reforestation efforts across the world.…”
Section: Resistance and Resilience Of Forest Ecosystemsmentioning
confidence: 99%
“…An incomplete understanding of the geographical distribution of an invasive species in uences the ability to accurately predict the consequences of invasions and the way in which policy makers should address invasion threats (Nagendra 2018). Research has suggested that tropical regions may be at less risk for invasion (Chong et al 2021), but more information is needed to assess if this pattern can be supported with data. Accurate invasion data are especially important when an invasion threatens economic stability (Angulo et al 2021).…”
Section: Introductionmentioning
confidence: 99%